Software and hardware engineering. Motorola M68HC12 - Cady, Fredrick M. (Oxford University Press, 2000)
Ideal for use in microprocessor courses in engineering or computer science, Software and Hardware Engineering: Motorola M68HC12 provides an in-depth, hands-on introduction to the architecture and design of hardware and software for the Motorola M68HC12